Gut microbiome in multiple myeloma: Mechanisms of progression and clinical applications - Zhang, Liuyun; Xiang, Yunhui; Li, Yanying; Zhang, Juan (Frontiers in Immunology, 2022)
The gut commensal microbes modulate human immunity and metabolism through the production of a large number of metabolites, which act as signaling molecules and substrates of metabolic reactions in a diverse range of biological processes. There is a growing appreciation for the importance of immunometabolic mechanisms of the host-gut microbiota interactions in various malignant tumors. Emerging studies have suggested intestinal microbiota contributes to the progression of multiple myeloma. In this review, we summarized the current understanding of the gut microbiome in MM progression and treatment, and the influence of alterations in gut microbiota on treatment response and treatment-related toxicity and complications in MM patients undergoing hematopoietic stem cell transplantation (HSCT). Furthermore, we discussed the impact of gut microbiota-immune system interactions in tumor immunotherapy, focusing on tumor vaccine immunotherapy, which may be an effective approach to improve anti-myeloma efficacy.